A Lithuanian, in Search the Meanings of Identity - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 1998)
The aim of the article is to analyze the meaning of the notion of Lithuanian identity. The analysis is developed in a few steps. First, the author looks into the role of nationalist images of the common in the eveday practices. The analysis is further developed, second, by noting that the concept of nationalism refers both to a word in a form of rhetorical practices and a thing in a form of social relations. Third, the author argues for a historical outlook that provides a possibility to understand the political ambiguities of nationalism.